2016
DOI: 10.1016/j.ecoleng.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon development in rejuvenated Indian coal mine spoil

Abstract: a b s t r a c tThe impact of mine spoil on the landscape is significant, as excavated rock-debris is commonly disposed in heaps that blanket the original land surface. Spoil heaps destroy the original soil habitat releasing soilbound carbon, which is difficult to re-estate when mining operations cease and restoration begins. The present work follows the development of vegetative cover on a coalmine spoil tip in India over a period of 19 years following restoration. The potential of re-vegetated the mine spoil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 47 publications
(25 reference statements)
0
21
1
Order By: Relevance
“…11 Distribution of total carbon (%), inorganic carbon (%), coal carbon (%) and biogenic carbon (%) of different reclaimed mine soil samples Rumpel et al (1998Rumpel et al ( , 2000 Old Reclaimed coal mines 4 0-10 8.7 43 Present study much higher than the reported values of 1.658 Mg C ha -1 year -1 (Singrauli, Tripathi et al 2014Tripathi et al , 2016, which is due to the younger age of site, however, it is expected that, rate of accumulation will decrease with age. Based on rate of SOC accumulation rate, C stock of RMS will reach close to the level of reference forest site is predicted as 15 years.…”
Section: Future Projection Of C Stockcontrasting
confidence: 53%
See 1 more Smart Citation
“…11 Distribution of total carbon (%), inorganic carbon (%), coal carbon (%) and biogenic carbon (%) of different reclaimed mine soil samples Rumpel et al (1998Rumpel et al ( , 2000 Old Reclaimed coal mines 4 0-10 8.7 43 Present study much higher than the reported values of 1.658 Mg C ha -1 year -1 (Singrauli, Tripathi et al 2014Tripathi et al , 2016, which is due to the younger age of site, however, it is expected that, rate of accumulation will decrease with age. Based on rate of SOC accumulation rate, C stock of RMS will reach close to the level of reference forest site is predicted as 15 years.…”
Section: Future Projection Of C Stockcontrasting
confidence: 53%
“…Studies across the globe on C sequestration through reclaimed coal mine soils have received considerable attention in recent past (IPCC 2000;Lal 2000, 2001;Ussiri and Lal 2005;Sperow 2006;Amichev et al 2008;Shrestha and Lal 2010;Tripathi et al 2014Tripathi et al , 2016Das and Maiti 2016). The CO 2 sequestration in reclaimed mine sites is calculated by estimating C-stock of biomass (aboveground and belowground), litter and reclaimed minesoils (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These changes accordingly increase the refractory carbon fractions, thereby enhancing soil carbon stability. The drop in ROC abundance is associated with a decrease in amino acids, carbohydrates, and other compounds in soils (Tripathi et al, ). Therefore, the abundance of labile fractions can be used as an effective index to estimate the alterations in carbon sequestration and soil fertility during forest restoration (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significant change in the composition and structure of plant community would have a crucial effect on labile carbon accumulation during forest restoration. It is not well known about how plants and soils regulate the variations in carbon pools during the restoration of tropical forests (Tripathi, Singh, & Hills, ). Therefore, identifying the dominant factors controlling the carbon dynamics could aid in determining the mechanism of soil carbon accumulation in tropical forests.…”
Section: Introductionmentioning
confidence: 99%
“…However, the need to meet the rising standard of living around the world has formed unfavourable impact on the environment and more so in the developing countries, like India which is striving to achieve the economic growth of 7.50% (www.tradingeconomics.com) for sustaining an ever-growing human population. It has resulted in over-exploitation of natural resources for different activities like deforestation, overgrazing, cultivation of marginal lands, mining and industrialization to meet the increasing demand for food, fuel and fiber (Areendran et al, 2013), influencing the topography, soil properties (Tripathi et al, 2009a), carbon storage, emission (Tripathi et al, 2014(Tripathi et al, , 2016 and plant productivity. Therefore, the land use change can be one of the best tools to understand the changes occurring due to mining and other allied industrial activities.…”
Section: Introductionmentioning
confidence: 99%